ASSESSMENT OF THE NUMBER OF T-CELL RECEPTOR EXCISION CIRCLE (TREC) AND KAPPA-DELETING RECOMBINATION EXCISION CIRCLE (KREC) IN CHILDREN WITH CONGENITAL HEART DEFECTS AND WITH FORCED THYMECTOMY - Shabaldin, Andrey Vladimirovich; Rovda, Yuri Ivanovich; Sinitskaya, Anna Viktorovna; Dadonova, Alena Vladimirovna; Shmulevich, Svetlana Aleksandrovna; Khalivopoulo, Ivan Konstantinovich; Chernykh, Natalya Stepanovna (Mother and Baby in Kuzbass, 2026)
The aim of this study was to evaluate the levels of TREC and KREC in children of the first year of life with congenital heart defects (CHD) and forced thymectomy.Copies of TREC, KREC and the IL17RA gene were quantified in isolated DNA from 100 µl of whole blood of 28 infants with congenital heart disease, represented by defects in the interventricular and interatrial septa, as well as their combinations with each other and with defects in the valves and blood vessels of the heart. The forced thymectomy was performed in 14 children (age 0.4 ± 0.2 years), the thymus was preserved (operation from a mini-access or by endovascular intervention) in 14 patients (age 1.1 ± 0.3 years).The study showed a positive correlation between the age of children and the level of TREC in peripheral blood, and a negative relationship between age and KREC levels. In children with congenital heart disease and forced thymectomy, the amount of TREC was significantly lower than in children with preserved thymus and conditionally healthy newborns. The number of KRECs in children with CHD and forced thymectomy was significantly higher than in children without it.Carrying out forced thymectomy in children of the first year of life in the surgical treatment of CHD is a risk factor for the formation of immunodeficiency states in them.
Keywords: TREC; KREC; congenital heart disease; forced thymectomy